FAKTOR - FAKTOR YANG MEMPENGARUHI PERSEPSI PENERIMAAN PAJAK PENGHASILAN - Siti Nurhidayati, 12.05.52.0204; Meita Oktaviani, Rachmawati (Students' Journal of Accounting and Banking, 2016)
This study aims to examine and analyze the effect of tax penalties, the service tax authorities, awareness of the taxpayer, and tax compliance against income tax revenue. This study used convenience sampling technique and survey method with questionnaires in collecting data. Respondent were sampled in this study is an individual taxpayer who performs is 120 respondent in Semarang Candisari KPP. Research data analysis using multiple analysis. The results showed that the variable tax penalties, awareness of the taxpayer, and tax compliance an effect on income tax revenue. The service tax authorities has no effect on income tax revenue.Keywords: Tax Penalties, The Service Tax Authorities, Awareness Of The Taxpayer, Tax Compliance, Income Tax Revenue